(Recht)Schreiben im Englischunterricht an der Primarschule - Ursula Bader; Steffi Vogt (Babylonia)
The article describes the research project “Writing in English Classrooms at Primary School” (Schreiben im Englischunterricht an der Primarschule), which is being carried out by the Chair for Learning and Teaching of English at the Institute for Primary Education PH FHNW and funded by the Department of Education, Culture and Sports of the Canton of Aargau. It presents preliminary results with regards to young learners’ spelling skills in the Canton of Aargau and England, the significance of writing and spelling in early foreign language classrooms, as well as principles of teaching writing at primary school level.